Fluorinated aminoanthranilamides: non-native amino acids for bringing proteomic approaches to charge-transfer systems. Issue 11 (6th March 2017) - Larsen-Clinton, Jillian M.; Espinoza, Eli M.; F. Mayther, Maximillian; Clark, John; Tao, Christina; Bao, Duoduo; Larino, Christa M.; Wurch, Michelle; Lara, Stephanie; Vullev, Valentine I.
Abstract : A highly selective substitution leads to a set of unique non-native amino acids that can serve as building blocks for molecular electrets. Abstract : The ability to control charge transfer at molecular and nanometer scales represents the ultimate level of electronic mastery, and its impacts cannot be overstated. As electrostatic analogues of magnets, electrets possess ordered electric dipoles that present key paradigms for directing transduction of electrons and holes. Herein we describe the design and development of fluorinated aminoanthranilamides, derivatives of non-native aromatic beta-amino acids, as building blocks for hole-transfer molecular electrets. A highly regio-selective nucleophilic aromatic substitution of difluorinated nitrobenzoic acid provides the underpinnings for an array of unprecedented anthranilamide structures. Spin density distribution and electrochemical analyses reveal that fluorine induces about 200 mV positive shifts in reduction potentials without compromising the stability of the oxidized residues, making them invaluable building blocks for hole-transfer systems. These findings open unexplored routes to novel amino-acid structures, setting a foundation for bringing principles of proteomics to designs of charge-transfer systems.